365 Epigenetic Profiling Reveals a Unique Histone Code in Chordoma. (1st August 2016) - Moussazadeh, Nelson; Berman, Samuel H.; Laufer, Ilya; Gounder, Mrinal; Zheng, Yupeng; Sommer, Joshua; Bilsky, Mark H.; Kelleher, Neil L.; Brennan, Cameron
Abstract: INTRODUCTION: Pathognomonic genetic "driver" lesions to explain the brachyury transcriptional program have not been described in chordoma. Herein we characterize the epigenetic histone, methyl-genomic, and somatic chromatin-modifying genotypic (CMG) landscape of chordoma. METHODS: Six chordomas with matched germline tissue representing a spectrum of location (sacral, clival, mobile spine), histopathology (classical and dedifferentiated), and stage (primary and postirradiation recurrences) underwent mass spectrometric histone profiling. Genotype was obtained via exome sequencing, and enhanced representation reduced bisulfite sequencing yielded genomic methylation data. RESULTS: Histone marks were highly conserved across chordoma samples regardless of site of origin or histopathology. Pathognomonic histone marks included hypermethylated lysine 27 on H3.1 (H3.1K27) compared with a cohort of 6 cancer cell lines ( P = 4.8e-10), marks associated with transcriptional repression. Other significant alterations included H3K4 hypermethylation, predicted on the basis of brachyury overexpression. Genotype further predicted some degree of variability across chordoma samples, with CMG alterations including lysine demethylase loss associated with hypermethylation at the predicted residues. CONCLUSION: In this first utilization of mass spectrometric analysis of a solid tumor, chordoma harbors a histone code distinct from other profiled neoplastic and normal tissues.